Interação do hidrogênio com a microestrutura dos aços inoxidáveis supermartensíticos sob regime elástico - Marques, Carlos Henrique da Fonseca (2018)
The Super 13Cr stainless steel - or supermartensitic - belongs in the 13Cr steel family with enhanced properties by the addition of alloy elements (like nickel and molybdenum) and reduced carbon. They present higher corrosion resistance under CO2, H2S, and chloride rich environments, and higher mechanical resistance and toughness. Therefore, under severe conditions, properties loss and hydrogen embrittlement may occur. With the understanding of mechanical stresses during manufacturing or operation, along with residual stresses, this work studied the interaction of hydrogen with the microstructure of the Super 13Cr steel under elastic loading. For the purpose of this work, hydrogen study, microstructure characterization and uniaxial tension tests (especially with hydrogenated samples under uniform stress) were made cooperatively with numerical analyses. The hydrogen interaction parameters and the microstructure were according to the literature, with the results being affected by the presence of strong trap sites like the remaining austenite. With increasing of time, cathodic current and applied load, advanced embrittlement were observed, i.e., higher ductility loss. About the elastic regime, the critical concentration of hydrogen for fracture was obtained. Locally, because of the mechanical state, higher concentrations were achieved increasing the probability of embrittling mechanisms to happen in a larger extension - leading to even greater losses in the material.